2011
DOI: 10.3109/19396368.2010.514022
|View full text |Cite
|
Sign up to set email alerts
|

Sperm and testis mediated DNA transfer as a means of gene therapy

Abstract: Assisted reproductive technologies (ART) have revolutionized the treatment of infertility. However, many types of infertility may still not be addressable by ART. With recent successes in identifying many of the genetic factors responsible for male infertility and the future prospect of whole individual human genome sequencing to identify disease causing genes, the possible use of gene therapy for treating infertility deserves serious consideration. Gene therapy in the sperm and testis offers both opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…It has been reported that exogenous DNA can stick to spermatozoa and then be carried into an egg via fertilization. This method of sperm mediation is widely used for gene transfer ( Parrington et al, 2011 ). Previous research has also investigated approaches for increasing the proportion of spermatozoa carrying exogenous DNA to improve the efficiency of transgenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that exogenous DNA can stick to spermatozoa and then be carried into an egg via fertilization. This method of sperm mediation is widely used for gene transfer ( Parrington et al, 2011 ). Previous research has also investigated approaches for increasing the proportion of spermatozoa carrying exogenous DNA to improve the efficiency of transgenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This method is designed to breed transgenic animals for use as preclinical models of human diseases, bioreactors for pharmaceutical products and in xenotransplantation experiments (Canovas et al, 2010;Parrington et al, 2011). Traditional and forced transfection methods for SMGT are electroporation, lipofection, DNA/ DMSO complexes, and restriction-enzyme-mediated integration.…”
Section: Embryogenesismentioning
confidence: 99%
“…In Table 1, a summary of previous studies on TMGT-related experiments is listed. Furthermore, there are several excellent papers reviewing the SMGT/TMGT-related studies [28,[90][91][92][93], which provide a helpful survey of this field. IIGT in mice.…”
Section: Introductionmentioning
confidence: 99%